Nozzle head design and simulation for higher interlayer strength of 3-D printed concrete - Hee, Yu Sheng (Nanyang Technological University, 2021)
3D Concrete printing (3DCP) is an emerging manufacturing technique that has the potential to vastly improve the processes involved in the civil engineering industry. At the forefront of all novel technologies is safety, where structural failure must be avoided at all costs. With 3DCP, not much research has been placed in investigating the resultant tensile strength of the extruded concrete, especially since the tensile strength of concrete is only 10% of its compressive strength. This study goes into detail on modifying the aspects of the nozzle head with the ultimate objective of maximizing the tensile strength of the concrete layers. Several techniques were used in this study, including Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA) simulations to model the concrete flow, as well as actual experiments to validate findings from the simulation analyses. Improvements were made on pre-existing methodology for the CFD modelling of 3DCP operations to improve accuracy and efficiency. The results from this study suggests that the usage of trowels would be essential in producing layers with smooth finishes and high tensile strengths, and the addition of a curved top trowel to shape the interface would further increase the interfacial strength between layers. The design iterations explored in this study had successfully improved the interface pressure by 255%, the interface shear stress by 9.6%, and the tensile strength by 107%. These extraordinary improvements to the interfacial properties will subsequently lead to a produced concrete structure with significantly higher tensile strengths. These findings also provide insights on the behaviour of the concrete flow as well as the optimization of tensile strength for future 3DCP operations.